Hubungan Kecukupan Asupan Kalsium dan Zat Besi dengan Derajat Dismenorea Primer pada Mahasiswi Ilmu Gizi Universitas Muhammadiyah Surakarta - Aprilia, Isna; Puspitasari, Dyah Intan; Mardiyati, Nur Lathifah; Sarbini, Dwi (JURNAL NUTRISIA, 2025)
Background: Dysmenorrhea, which is the condition of cramps or pain during menstruation, can be caused by various factors, including inadequate intake of calcium and iron. Objective: This study aims to analyze the relationship between the adequacy of calcium and iron intake and the severity of primary dysmenorrhea among nutrition students at Universitas Muhammadiyah Surakarta. Method: A cross-sectional design was used in this study with a sample of 140 female students at Nutrition Science in UMS. Simple random sampling was utilized for sample collection. The WaLIDD scale questionnaire was used to calculate dysmenorrhea scores, and the SQ-FFQ form was employed to assess the adequacy of calcium and iron intake over the past month. Data analysis was conducted using the Spearman Rank test. Results: The findings indicate that all students experienced dysmenorrhea, with an average calcium intake adequacy of 36.3% and an average iron intake adequacy also categorized as insufficient (42.4%). From the Spearman Rank test analysis, the adequacy of calcium intake related to dysmenorrhea showed a p-value of 0.450, and iron intake adequacy related to dysmenorrhea had a p-value of 0.244. Conclusion: There is no significant relationship between the adequacy of calcium and iron intake and the severity of primary dysmenorrhea among the nutrition students at Universitas Muhammadiyah Surakarta. It is recommended that future researchers can conduct blood serum measurements to assess calcium and iron levels to prevent dysmenorrhea.